Investigation of heat and mass transfer of free convective MHD flow along a vertical plate in a porous medium using the new modified differential transform-decomposition method - Helena Nayar; Patrick Azere Phiri (Results in Engineering)
In this paper, the recently developed New Modified Differential Transform-Decomposition Method is applied for the first time for solving the magneto-hydrodynamic flow problem of a Newtonian fluid along an infinite vertical plate. The plate is assumed to be immersed in a porous medium and is subjected to a transverse magnetic field. Induced magnetic and electric fields are ignored, just as radiative heat flux is considered to be negligible. Presence of heat sink and first order chemical reaction are assumed. No slip boundary conditions are considered at the plate. The solutions obtained are validated by comparing them with Laplace Transform solutions from a previous study. The heat and mass transfer properties of the flow are analyzed for various parameters with the help of 2d plots. Influence of the parameters on skin friction, Nusselt number and Sherwood number is also studied. The method is found to be applicable directly to the boundary value problem, and successful in producing analytic solutions.